An introduction to Christian ethics: history, movements, people - Huebner, Harry J. (Baylor University Press, 2012)
Christian ethics is theology embodied in the lives of real people. Matters of justice, poverty, power, and violence often lack the appropriate Christian practice of the "Word becoming Flesh." In this comprehensive volume, Harry Huebner skillfully addresses the ethical challenges raised by social philosophers as well as Latin American, African American, Aboriginal, feminist, and peace theologians. An Introduction to Christian Ethics spans the centuries--from Athens to contemporary America and beyond--and collects some of the most influential voices in Christian ethics on both classical theories and contemporary moral issues. Huebner's careful presentation allows each of these voices--and their distinctive cultural settings--to ring through history and across social boundaries. Huebner provides teachers and students with a solid foundation upon which to build a faithful approach to ethical thought and practice